Discovering The Truth in Fratelli Tutti (The Macau Ricci Institute Journal, 2023)
Pope Francis’ recent encyclical, Fratelli tutti (2020), is an important resource for understanding the attempt to contribute to a new economic paradigm, outlined in the “Macau Manifesto”.  But the encyclical is very long, and readers may not feel ready to devote so much time to absorbing its meaning.  The following essay is an attempt to interpret the themes and outline the main points of the encyclical, so that readers of the MRIJ can appreciate its significance, and thus the importance of the “Macau Manifesto” as a response to its message.